ABOUT THERMAL STABILITY OF BISMUTH(III) IODINE ETIOPORPHYRIN II COMPLEX - D. V. Golubev; V. D. Rumyantseva; V. V. Fomichev (Тонкие химические технологии, 2017)
For the first time, a complex of bismuth(III) with iodine and etioporphyrin II is reported. It was prepared by reacting etioporphyrin II and bismuth(III) iodide in pyridine in Ar atmosphere. The prepared compound was characterized by FT-IR, 1H-NMR, UV-VIS spectroscopy and mass spectrometry. One intense line at m/z 684.990 attributed to the complex without the iodine atom is observed in the mass spectrum. This is in agreement with the data indicating that bismuthporphyrin complexes generally have low stability. Analysis of FT-IR spectra obtained at room temperature and at 145°С is reported. Priroda15 DFT package was used for optimization of complex geometry and calculation of the IR spectrum. Calculations were done using BPE functional and L1 basis set under relativistic approximation of Dyall Modified Dirac. Assignment of the vibrational frequencies is reported. Collected data indicate that the complex of bismuth(III) with iodine and etioporphyrin II is not stable and easily hydrolyses when exposed to air forming the corresponding hydroxocomplex. This transformation does not change significantly the dynamics of the porphyrin ring.